Applying The 5w + 1h Method In English Teaching For Madrasah Ibtidaiyah Students - Salsabila, Nasywa; Pawira, Elsa Adinda Suci Sugi; Fitriani, Auliah; Nasution, Salsabila (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to investigate the effectiveness of the 5W + 1H method in enhancing English language skills among Madrasah Ibtidaiyah students. The 5W + 1H method, which stands for Who, What, Where, When, Why, and How, is a popular journalistic technique used to gather information and structure a story. This method can be adapted to English language teaching to encourage students to ask questions, develop critical thinking, and improve their communication skills. The study employed a quasi-experimental design, involving 30 students from a Madrasah Ibtidaiyah in Indonesia. The results showed that the experimental group, which received the 5W + 1H method instruction, outperformed the control group in terms of English language skills, including reading, writing, and speaking. The students' responses to the questionnaire indicated that they enjoyed the learning process and felt more confident in using English. The study suggests that the 5W + 1H method is an effective approach to teaching the English language to Madrasah Ibtidaiyah students, promoting interactive and collaborative learning, critical thinking, and problem-solving skills. The findings have implications for English language teaching in Madrasah Ibtidaiyah settings, providing a framework for teachers to create a more engaging and effective learning environment.